KONFLIK SOSIAL KEPEMILIKAN LAHAN MASYARAKAT ADAT KENEGERIAN SIBERAKUN KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Surya Pili; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted in the operational area of PT. Duta Palma Nusantara Sei Kuko' to be precise in Benai Regency. The  purpose of this study was to find out how the conflict occurred and the source of social conflict between PT Duta Palma Nusantara and the indigenous people of Kenegerian Siberakun, Benai District, Kuantan Singingi Regency. This study uses a qualitative descriptive research method. As a subject in this study amounted to 15 people. The technique of determining the informants is by using purposive sampling technique. namely taking the subject by setting criteria or special characteristics or certain characteristics that are in accordance with the research objectives so that they can answer research problems. In collecting data, researchers used observation, interviews and documentation. The forms of conflict that occurred between PT Duta Palma Nusantara and the indigenous people of Kenegerian Siberakun, Benai Regency, such as the burning of an Excavator unit by an emotional community, open demonstrations to the Regent's Office, DPRD Kuantan DPRD Singingi Regency and Riau Province and filing cases . to the Court/Supreme Court, While the background of the social conflict is the issue of cooperation with the Hak Guna Usaha (HGU) in the utilization, management of land on an area of 11,260 Ha to the for 25 years starting from 1997 ending in 2018 but being extended unilaterally by PT. Duta Palma Nusantara until 2043 unilaterally without notifying the land owner, namely the indigenous people of Kenegerian Siberakun.  Keywords:  Social Conflict, Land, Indigenous Peoples of the Siberakun Country